STRATEGI KEBERHASILAN GURU DALAM MENGELOLA KELAS UNTUK MENCAPAI TUJUAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SDN KARANG ASIH 09 - Alifiah Nursifa; Amirudin; Yadi Fahmi Arifudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Class Management is an integral component in the learning process that affects the interaction between teachers and students as well as the learning environment within the classroom. This study aims to investigate effective strategies in class management that have been developed and applied in various educational contexts. The research findings show that there are various strategies that can enhance the effectiveness of class management, including the application of clear rules, the formation of positive relationships between teachers and students, and a responsive approach to individual student needs. Additionally, the integration of developmental psychology principles and conflict management has been proven effective in creating a conducive learning environment. This study contributes to educational practitioners by presenting a comprehensive framework for class management, highlighting the importance of aligning strategies with classroom contexts and student characteristics. Practical implications and directions for further research are also discussed to deepen understanding about the dynamics of high-quality class management in supporting learning objectives.